Economic analysis of agricultural production and labour utilization among the Hausa in the North of Nigeria - Norman, D. W. ([S.l.] : Michigan State University, Department of Agricultural Economics, 1973)
This case study examines in some detail the farming practices and production of Moslem farmers in Zaria area which is situated in the northern part of the Guinea zone
osc 25/03/2019
Loans